2020
DOI: 10.1055/s-0040-1721848
|View full text |Cite
|
Sign up to set email alerts
|

Lung Ultrasound for Predicting the Respiratory Outcome in Patients with Bronchopulmonary Dysplasia

Abstract: Objective This study aimed to investigate the utility of lung ultrasound (LUS) with whole chest scanning for predicting respiratory outcomes in patients with bronchopulmonary dysplasia (BPD). Study Design We performed a prospective observational study. Preterm infants of less than 32 weeks' gestational age requiring oxygen therapy at 28 days of life were included. LUS was performed on day 28, at 36 weeks' postmenstrual age, and at the time of discharge. Each lung was divided into three regions by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 41 publications
0
14
0
5
Order By: Relevance
“…A contemporary definition of BPD that correlates with respiratory morbidity in childhood is needed [31]. Also, a new lung ultrasound technique for predicting the respiratory outcome in patients with BPD can be used instead of HRCT [32].…”
Section: Discussionmentioning
confidence: 99%
“…A contemporary definition of BPD that correlates with respiratory morbidity in childhood is needed [31]. Also, a new lung ultrasound technique for predicting the respiratory outcome in patients with BPD can be used instead of HRCT [32].…”
Section: Discussionmentioning
confidence: 99%
“…First, the scoring of LUS images is not complicated. Recently, a LUS scoring system has been used for the diagnosis and management of respiratory distress syndrome [26][27][28][29][30][31] , predicting the development of BPD [32][33][34] , and evaluating pulmonary water content 35 . In contrast, radiographic evaluation is subjective, which minimizes its generalizability and reproducibility 36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…In most of the studies carried out to date, LUS were shown to be able to predict the development of BPD as early as 7-14 days of life, with a predictive cut-off value ranging between 4 and 10. 17, [30][31][32][33][34][35][36][37] Although BPD is a disease characterized by a non homogeneous lung picture 41 with particular involvement of the gravity-dependent areas, 42 the inclusion of posterior areas in the LUS does not seem to improve the predictive characteristics as demonstrated by Alonso-Ojembarrena et al 36 and in the recent meta-analysis published by Pezza et al 43 A novel approach was proposed by Raimondi et al who developed a logistic regression model to describe the interaction between GA and LUS in predicting BPD. 17 Similar results were obtained from the model proposed by Aldecoa Bilbao et al 37 These models had a higher predictive capacity compared to the LUS alone.…”
Section: Lung Ultrasound Score and Prediction Of Bronchopulmonary Dys...mentioning
confidence: 99%